ANTIMICROBIAL EFFECT OF A MEANS FOR ENZYME EXCAVATION (BRIX 3000) AND PHOTODYNAMIC THERAPY IN CARIOUS LESIONS OF PRIMARY TEETH - IN VITRO EXPERIMENT - Zornitsa Lazarova; Maya Rashkova; Raina Gergova; Virna-Maria Stavros Tsitou (Peytchinski Publishing, 2021)
The selective removal of the caries dentin via enzyme methods for excavation appears to be an alternative to the conventional treatment of carious lesions in childhood. Photodynamic therapy is an effective alternative for the reduction of cariesogenic microorganisms. Brix 3000 is an enzyme-based material for excavation of carious dentin. Aim: To study the antimicrobial effect of means for enzyme excavation (Brix 3000) and photodynamic therapy with FotoSan 630 Intro Kit to the two main cariesogenic microorganisms - S. mutans and L. acidophilus, in vitro experiment; Materials and Methods: Eighty plates were prepared: group 1- 20 plates only with Brix 3000; group2 - 20 plates only with FotoSan; group 3 - 20 plates with a combination of Brix 3000 and FotoSan; group 4 - 20 plates without an active agent. In the agar of each plate, three 7 mm wells in diameter were made, where the Brix 3000 gel was placed, as well as discs soaked with the dye and irradiated with FotoSan and a combination of them. After 24 hours, the zone of inhibition was measured. Results: Compared to the control group, Brix 3000 and FotoSan have a defined antimicrobial activity against S. mutans and Lactobacillus spp. By combining the two materials, their antimicrobial activity significantly increases. S. mutans shows greater resistance compared to Lactobacillus spp. Conclusion: A combination of enzyme-based excavation and photodynamic therapy could be used successfully in the treatment of carious lesions in primary teeth.